2016
DOI: 10.1007/s10734-016-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Drifting apart or converging? Grades among non-traditional and traditional students over the course of their studies: a case study from Germany

Abstract: Since 2009, German universities were opened by law to freshmen who do not possess the traditional graduation certificate required for entry into University, but who are rather vocationally qualified. In this article, we track the grades of these so-called nontraditional students and compare them to those of traditional students using a longitudinal design. Based on assumptions about differences in competencies, family background and the cultural closeness of academia, we derive hypotheses on differences concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Statistics show that non-traditional university students are less likely than their traditional counterparts to achieve higher degree classifications, even with the same entry grades (HEFCE 2014;Richardson 2015). Similar patterns have also been reported in Australia (Gale and Tranter 2011), Germany (Brändle and Lengfeld 2017) and the United States (Braxton 2000).…”
Section: Non-traditional Students At Universitymentioning
confidence: 61%
“…Statistics show that non-traditional university students are less likely than their traditional counterparts to achieve higher degree classifications, even with the same entry grades (HEFCE 2014;Richardson 2015). Similar patterns have also been reported in Australia (Gale and Tranter 2011), Germany (Brändle and Lengfeld 2017) and the United States (Braxton 2000).…”
Section: Non-traditional Students At Universitymentioning
confidence: 61%
“…Nevertheless, in their study these lower grades also translated into lower completion rates. On the other hand, Brändle and Lengfeld (2017) found consistently lower performance among non-traditional students throughout their complete course of studies. Moreover, they noted that non-traditional students had lower course completion rates at the beginning of their studies, less frequently obtained a degree, and, when they did, received worse grades than traditional students did (Brändle & Lengfeld, 2015).…”
Section: Study Performancementioning
confidence: 86%
“…These differences can create success barriers because higher education's structure is not designed to meet nontraditional student needs (Erisman and Steele 2012;Gilardi and Guglielmetti 2011;Munro 2011). Brandle and Lengfeld (2017) reported that nontraditional students have a different habitus than traditional students and that the learning environment is not inclusive of their needs. Research by Lawrence (2005) and Smit (2012) found that instructors see nontraditional students as having deficits in their ability or skills needed to succeed.…”
Section: Meeting Student Needs: Changing Student Populationsmentioning
confidence: 99%